PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH DENGAN MENGGUNAKAN LKPD UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF PESERTA DIDIK KELAS XII MIA 2 SMA NEGERI 1 TEWANG SANGALANG GARING TAHUN PELAJARAN 2019/2020 PADA MATERI SEL VOLTA - Fiska Purwanita (Universitas Papua, Manokwari, Indonesia, 2019)
AbstractThis research is a Classroom Action Research that aims to improve cognitive learning outcomes for Class XII MIA 2 Students at SMA Negeri Tewang Sangalang Garing TP 2019/2020 Voltaic Cell Material. In this study using 3 cycles. The results showed that there was an increase in student learning outcomes after the application of the problem-based learning model using LKPD, an increase of 43.08%. classical completeness of cycle i reached 54.55%, cycle ii was 72.73%, and cycle iii was 100%. Keywords: Learning Outcomes, Problem Based Learning, Classroom Action Research, Voltaic Cells